2015
DOI: 10.1007/s11749-015-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

Robust estimation of multivariate location and scatter in the presence of cellwise and casewise contamination

Abstract: Multivariate location and scatter matrix estimation is a cornerstone in multivariate data analysis. We consider this problem when the data may contain independent cellwise and casewise outliers. Flat data sets with a large number of variables and a relatively small number of cases are common place in modern statistical applications. In these cases, global down-weighting of an entire case, as performed by traditional robust procedures, may lead to poor results. We highlight the need for a new generation of robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 17 publications
1
112
0
Order By: Relevance
“…We have shown that exact affine equivariance must be lost, but it is a reasonable price to be paid in order to achieve an arbitrarily high breakdown for the resulting trimmed estimators. This conclusion parallels similar findings in other situations where contamination produces only a minority of “good” observations, as in the case of cellwise contamination (see, e.g., Farcomeni, , ; Agostinelli, Leung, Yohai, & Zamar, ; Rousseeuw & Van den Bossche, ). We also support the use of adaptive trimming schemes, in order to explore the effect of different levels of trimming and to find a sensible trade‐off between robustness and efficiency.…”
Section: Discussionsupporting
confidence: 88%
“…We have shown that exact affine equivariance must be lost, but it is a reasonable price to be paid in order to achieve an arbitrarily high breakdown for the resulting trimmed estimators. This conclusion parallels similar findings in other situations where contamination produces only a minority of “good” observations, as in the case of cellwise contamination (see, e.g., Farcomeni, , ; Agostinelli, Leung, Yohai, & Zamar, ; Rousseeuw & Van den Bossche, ). We also support the use of adaptive trimming schemes, in order to explore the effect of different levels of trimming and to find a sensible trade‐off between robustness and efficiency.…”
Section: Discussionsupporting
confidence: 88%
“…The devastating effect of combined cellwise and casewise outliers on standard robust estimates has recently been discussed in Agostinelli et al (2015) who introduced a second generation of robust estimates that can deal simultaneously with these two DQ issues. These procedures can also be used to summarize and analyse AD.…”
Section: Daniel L Oberski (Utrecht University)mentioning
confidence: 99%
“…However, as for the original estimate, computation times are not feasible for larger numbers of variables. A very recent approach by Agostinelli et al [2015] flags cellwise outliers as missing values and applies afterwards a rowwise robust method that can deal with missing values. By this, it can deal with cellwise and rowwise outliers at the same time, but again, computation for high-dimensions is not achievable.…”
Section: Introductionmentioning
confidence: 99%